Vonoprazan: a promising advancement in proton pump inhibitor therapy - Vinayagam, Shanmugapriya; Mittal, Niti; Kaushal, Jyoti (International Journal of Basic & Clinical Pharmacology, 2024)
Vonoprazan, a potent potassium-competitive acid blocker (P-CAB), has emerged as a potential therapeutic option for acid-related disorders, particularly gastroesophageal reflux disease (GERD) and peptic ulcer disease (PUD). This comprehensive review aims to provide an overview of the efficacy, safety profile, and clinical implications of vonoprazan based on current literature. Efficacy studies have demonstrated vonoprazan's superiority over proton pump inhibitors (PPIs) in achieving effective acid suppression, rapid symptom relief, and promoting mucosal healing in patients with GERD and PUD. Moreover, its long-lasting acid suppression properties offer protection against Helicobacter pylori (H. pylori) infection, presenting it as a potential alternative to traditional triple H. pylori eradication regimens. Safety evaluations reveal a favourable tolerability profile with minimal adverse effects and a lower risk of drug interactions compared to PPIs. However, concerns regarding long-term safety, such as hypomagnesemia and the potential for rebound acid hypersecretion, necessitate further investigation. Additionally, the role of vonoprazan in special populations, such as the elderly and those with renal impairment, warrants exploration. Overall, vonoprazan represents a promising advancement in acid suppression therapy, offering efficacy, safety, and potential advantages over traditional agents.